Electric field induced structural, magnetic and ferroelectric properties of 0.6PbFe0.5Nb0.5O3-0.4BiFeO3 multiferroic solid solution. Issue 17 (1st December 2020) - Dadami, Sunanda T.; Rayaprol, Sudhindra; Sathe, Vasant; Angadi, Basavaraj
Abstract: In this paper, 0.6PbFe0.5 Nb0.5 O3 -0.4BiFeO3 (PBFN) multiferroic was electrically poled at room temperature. The influence of electric poling on structure was studied in detail by XRD and Raman measurements. The poling impacts on magnetic and ferroelectric properties were studied through susceptibility and ferroelectric measurements. XRD analysis of the poled sample exhibits the strengthening of Fe/Nb/Bi–O bonds. Raman measurements were carried out at different temperatures (300 K–650 K). Raman spectra of the unpoled sample exhibited seven active modes at 254, 470, 566, 684, 804, 979 and 1111.1 cm −1 at room temperature. The poled sample showed change in intensity around Bi–O and Fe–O modes due to spin-phonon coupling. Temperature dependent magnetization measurements revealed the presence of converse magnetoelectric effect. Ferroelectric measurements showed the influence of electric poling with increase in coercive field. Hence, controlling the magnetization with electrical poling finds more potential applications in multiferroics.